Determinan Tax Avoidance: Kualitas Audit Sebagai Variabel Moderasi Menggunakan Regression Analysis - Yulia Agustina; Swarmilah Hariani (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
Tax avoidance is a transaction scheme aimed at minimizing the tax burden by taking advantage of the weaknesses in a country's tax provisions, so that tax experts state that it is legal because it does not violate tax regulations. This study aims to determine and examine the effect of institutional ownership, managerial ownership, and leverage on tax avoidance with audit quality as a moderating variable. The data source in this study is the financial statement data of retail companies listed on the Indonesia Stock Exchange for the period 2018-2022. The total population was obtained as many as 32 companies, then the sample of this study was obtained by purposive sampling technique which resulted in a sample of 27 companies for further research. The analysis technique used is multiple linear regression analysis managed through SPSS 25. The results of this study indicate that institutional ownership affects tax avoidance, while managerial ownership, and leverage have no effect on tax avoidance. In addition, this study shows that audit quality is able to moderate institutional ownership, managerial ownership, and leverage on tax avoidance.